Health inequities in functional limitation among Mexican older adults: An intersectional approach - Héctor García-Hernández; Guillermo Salinas-Escudero; Hortensia Reyes-Morales; María Fernanda Carrillo-Vega (PLoS ONE, 2025)
Functional limitation represents a major health concern among older adults, with its incidence increased based on personal characteristics such as being a woman, having minor levels of education, and lower socioeconomic status, leading to health inequities. Addressing these inequities requires comprehensive frameworks like intersectionality to provide a broader perspective. This study analyzes health inequities in functional limitation among Mexican older adults using data from the 2021 round of the Mexican Health and Aging Study (MHAS) within an intersectional framework. The Multilevel Analysis of Individual Heterogeneity and Discriminatory Accuracy (MAIHDA) technique, recognized as the gold standard in quantitative intersectionality research, was employed. Six variables were assessed: age, sex, education, social engagement, economic status, and access to health services. The results indicate that age, social engagement, and economic status were the main variables that explain functional limitation. Enhancing social engagement emerges as a practical short-term strategy to improve functionality and reduce inequities. Contrary to prior evidence, sex was not directly associated with functional limitation. Therefore, higher rates of functionality loss previously reported in the literature may not simply be linked to being a woman but rather to the societal implications of being a woman in contemporary contexts. Similarly, access to health services did not show a significant relationship with functional limitation despite the health system being a critical intermediate social determinant of health with the potential to address inequities. This research underscores the importance of intersectionality in understanding inequality, offering a nuanced perspective on overlapping systems of oppression and privilege to address disparities in Mexican older adults.